IL-18-primed NK cells recruit dendritic cells and potentiate tumor therapy mediated by PD-1 blockade - Ohno, Yoshiya; Okamura, Haruki; Yagita, Hideo; Tanaka, Toshiyuki (Frontiers in Oncology, 2025)
The success of cancer immunotherapy depends on the effective coordination of innate and adaptive immunity. We previously reported that IL-18 potentiates the therapeutic effects of immune checkpoint inhibitors in mouse models. Here, we report that IL-18-primed natural killer (NK) cells enhanced the antitumor effects of anti-PD-1 antibodies by mobilizing type 1 conventional dendritic cells (cDC1s) to tumor sites and promoting type 1 immune responses. IL-18-primed NK cells had a premature phenotype, and expressed chemokines involved in cDC1 mobilization. In a combination treatment with IL-18 and anti-PD-1 antibody, NK cell depletion inhibited cDC1 mobilization and abrogated the therapeutic effects. Additionally, adoptive transfer of IL-18-primed NK cells induced cDC1 mobilization and enhanced the therapeutic effects of anti-PD-1 antibodies. IL-18 also increased IL-12 mRNA expression in DCs and IL-12 blood levels, and IL-12 upregulated XCL1 expression in NK cells. These results suggest that IL-18 primes NK cells and enhances the therapeutic effects of immune checkpoint inhibitors by promoting a feed-forward loop involving DCs.